2020
DOI: 10.1108/ijif-01-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Are Islamic mutual funds exposed to lower risk compared to their conventional counterparts?

Abstract: Purpose This study aims to comparatively analyze the systematic, idiosyncratic and downside risk exposure of both Islamic and conventional funds in Pakistan to see which of the funds has higher risk exposure. Design/methodology/approach The study analyzes different types of risks involved in both Islamic and conventional funds for the period from 2009 to 2016 by using different risk measures. For systematic and idiosyncratic risk single factor CAPM and multifactor models such as Fama French three factors mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Muslims' decision-making in the context of investing in Sharia assets is also negatively influenced by their risk attitude. Naveed, Khawaja, and Maroof (2020) stated that sharia investments have a lower risk exposure compared with conventional investments. Meanwhile, León and Pfeifer (2017) found that Muslims are less risk-taking in financial matters compared to those from other religions.…”
Section: Discussionmentioning
confidence: 99%
“…Muslims' decision-making in the context of investing in Sharia assets is also negatively influenced by their risk attitude. Naveed, Khawaja, and Maroof (2020) stated that sharia investments have a lower risk exposure compared with conventional investments. Meanwhile, León and Pfeifer (2017) found that Muslims are less risk-taking in financial matters compared to those from other religions.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of study to compare Muslim motivation toward comparative study between conventional and Islamic banks. The other weakness of prior studies is more prone to examine a decision-making process, which mainly uses correlation and cross-sectional techniques such as surveys (Adil, 2021; Hassan et al , 2018; Naveed et al , 2020). Hence, fall to provide comprehensive results on Muslim behavior on Islamic banks even though some scholars found consumers more inclined to adopt conventional banks than Islamic banks in some Muslim countries.…”
Section: Introductionmentioning
confidence: 99%
“…This study creates a CG index comprising several governance rules in accordance with the SECP 1 ’s CG recommendations to examine the role of CG quality in the dividend distribution decisions of socially responsible enterprises. Previous studies, such as Samaha et al (2012) ; Javaid and Saboor (2015) , and Naveed et al (2020a) , developed a CG index that included a variety of governance mechanisms to assess the CG quality. Following the above studies, a comprehensive CG index is constructed where the higher total score represents the highest quality.…”
Section: Methodology and Datamentioning
confidence: 99%